POVERTY ALLEVIATION IN SOUTH AFRICA: THE ROLE OF AGRICULTURE EDUCATION AND MECHANIZATION - (:unkn) unknown (My University, 2022)
The need to reduce poverty and increase agricultural production has been the priority of emerging economies. Poverty is one of the significant developmental challenges affecting the development of South Africa after the 1994 apartheid. Recent statistics indicated that about 49.2% of citizens aged 18 falls below the upper-bound poverty line in South Africa. Therefore, various mechanisms are being implemented to alleviate poverty in South Africa. Sustainable agricultural mechanization is a pivotal contributor to the development of agricultural productivity.The study employed a content analysis technique to approach the significant objective of the research. Discussion from the study shows that poverty can be alleviated through agriculture mechanization when; there is a reduction in food prices, improved farm income, created jobs through agriculture, and increased farm productivity. The study also indicated that effective agricultural mechanization implementation could be achieved by including agriculture mechanization modules in the South African educational system, enhancing the agricultural sector’s innovation and profitability, and establishing a training base for enterprises.Government must therefore create an enabling environment for the development of agriculture mechanization in South Africa. Agricultural mechanization can be promoted by providing local farmers subsidies and credit loan facilities, capacity building and training, and research and development.
Keywords: African Research